Antibacterial activity of mixed Dukung Anak (Phyllanthus niruri) Oil and Kaffir Lime (Citrus hystrix) Oil against pathogenic bacteria - Hassan, Nurul Aini (2019)
The medicinal plant has their variety in term of benefit, advantages and it has their own significant. Medicinal plant like Dukung Anak (Phyllanthus niruri) have some problems which do not have enough research compare the other Phyllanthus sp. while the Kaffir lime (Citrus hystrix) usually are been used as the antibacterial agent. This study are to see the correlates between the mixed oil from the Dukung Anak (Phyllanthus niruri) oil and Kaffir Lime (Citrus hystrix) oil. The oil of the plant gets from the extraction process by using the steam distillation method and separating process. Both of the plants undergoes the same process to get the oil. As the result, the yield of the Dukung Anak (Phyllanthus niruri) is 0.26 % and Kaffir Lime (Citrus hystrix) is 3.01 %. The concentration of mixed oil (60µl, 70 µl & 80 µl) are used to see the zone inhibition of bacteria like Staphylococcus aureus and Escherichia coli. Overall, test towards A1 (60 µl) give the best inhibition of zone and show the effectiveness even there are only 10 µl of Dukung Anak (Phyllanthus niruri) oil and 50 µl of Kaffir lime (Citrus hystrix) oil. In ANOVA result, both experiments can be concluded that the null hypothesis that makes are been acceptable. As conclusion, all the objective have been achieved.